Congenital infections (syphilis and human immunodeficiency virus) in a federal hospital in Rio de Janeiro - Moura, Márcia Saldanha dos Santos; Figueiredo Junior, Israel; Pinheiro, Fátima Maria Campinho; Lima, Diana Almeida de (Brazilian Journal of Sexually Transmitted Diseases, 2021)
Introduction: Congenital infections are related to a higher risk of morbidity and mortality in the neonatal period and can cause serious complications in the newborn. Among the sexually transmitted infections (IST) present in this group, syphilis and vertical exposure to the human immunodeficiency virus (HIV) are still a challenge in the 21st century. Objective: To evaluate the prevalence of congenital syphilis and exposure to HIV among congenital infections. Methods: Cross-sectional, analytical study with data collected from medical records of newborns admitted to the Conventional Neonatal Intermediate Care Unit, Kangaroo and Joint Accommodation, in the database of the service of the Federal Hospital from Bonsucesso, from January 2015 to December 2018. Results: During the study, 2,202 newborns were discharged from the hospital and 474 were positive for congenital infection (21.8%). In cases of congenital infection, congenital syphilis (398–84%) and maternal HIV infection (40–8,4%) were the most frequently encountered clinical situations. The relationship between prenatal care and the absence of congenital infection was evident. Among the newborns, 117 (5.3%) were premature, 352 (16.3%) were older than 37 weeks and 95 (23.7%) had low birth weight. Conclusion: Congenital infection was one of the main causes of neonatal morbidity; syphilis and HIV had the highest prevalence, being associated with reducible deaths when adequate care is provided for women during pregnancy. Perinatology services demand a great effort in order to manage these avoidable and undesirable situations.